A Helical Polypeptide‐Based Potassium Ionophore Induces Endoplasmic Reticulum Stress‐Mediated Apoptosis by Perturbing Ion Homeostasis. Issue 14 (24th May 2019) - Lee, DaeYong; Lee, Soo‐Hwan; Noh, Ilkoo; Oh, Eonju; Ryu, Hyunil; Ha, JongHoon; Jeong, SeongDong; Yoo, Jisang; Jeon, Tae‐Joon; Yun, Chae‐Ok; Kim, Yeu‐Chun
Abstract: Perturbation of potassium homeostasis can affect various cell functions and lead to the onset of programmed cell death. Although ionophores have been intensively used as an ion homeostasis disturber, the mechanisms of cell death are unclear and the bioapplicability is limited. In this study, helical polypeptide‐based potassium ionophores are developed to induce endoplasmic reticulum (ER) stress‐mediated apoptosis. The polypeptide‐based potassium ionophores disturb ion homeostasis and then induce prolonged ER stress in the cells. The ER stress results in oxidative environments that accelerate the activation of mitochondria‐dependent apoptosis. Moreover, ER stress‐mediated apoptosis is triggered in a tumor‐bearing mouse model that suppresses tumor proliferation. This study provides the first evidence showing that helical polypeptide‐based potassium ionophores trigger ER stress‐mediated apoptosis by perturbation of potassium homeostasis. Abstract : The perturbation of potassium homeostasis is a promising strategy for the induction of apoptosis . Novel potassium ionophores disturbing ion homeostasis, thereby inducing endoplasmic reticulum stress‐mediated apoptosis in vitro and in vivo, are developed. This work reports the apoptotic mechanism by perturbing ion homeostasis, and also shows the bioapplicability as a potential anticancer agent.